Perubahan Struktur Keluarga Kajang Luar Akibat Akses Pendidikan dan Teknologi Digital - Arianti, Dina; Hairunnisa, Apifah; Agustiawan, Rinaldi; Awaru, A.Octamaya Tenri (Indo-MathEdu Intellectuals Journal, 2025)
Access to education and advances in digital technology have had a significant impact on many communities, but their impact on indigenous peoples is not always immediate. This study aims to analyze how access to education, digital technology, and their interactions influence family structure, communication styles, and gender norms in the Kajang Luar community. The study used a qualitative descriptive approach, using interviews and observation. Data were analyzed using a thematic categorization process to identify consistent patterns in the narrative information. The study findings indicate that education has not changed family structure in Kajang Luar because customary values (Pasang ri Kajang) remain a primary factor in family life. Education is not seen as a driver of change in power relations within the family, but rather as a tool influenced by knowledge and occupation. In terms of digital technology, the Kajang Luar community has selectively adopted mobile phones since the COVID-19 pandemic in 2020 to meet the needs of online education. Although technology facilitates access to communication and information, its use remains filtered according to customary values, resulting in no significant changes in family interactions. In terms of gender, education and technology have not fundamentally shifted the roles of men and women, although there are indications of minor changes in the younger generation due to exposure to external values.